Targeting Neurofibromin 2 (NF2) prevents endothelial dysfunction in obesity: a study in mice and humans. (3rd October 2022) - Costantino, S; Mohammed, S A; Gorica, E; Ambrosini, S; Akhmedov, A; Virdis, A; Ruschitzka, F; Masi, S; Paneni, F
Abstract: Introduction: The mechanisms underlying endothelial dysfunction (ED) in obesity are poorly understood. Neurofibromin 2 (NF2) is a scaffold-like protein involved in cell growth and survival. However, its role in the vascular endothelium is unknown. Purpose: To investigate NF2 function in obesity-related ED. Methods: Human aortic endothelial cells (HAECs) were exposed to palmitic acid (PA, 200 uM) or vehicle for 48 hours. Gene silencing of NF2 was performed by small interfering RNA (siRNA). Gene and protein expression were assessed by real time PCR and Western blot, respectively. The interaction of NF2 with endothelial proteins was investigated by co-immunoprecipitation. A constitutive active mutant form of NF2 (Ala518) was employed to study the effects of NF2 gain-of-function. To specifically investigate NF2 role in the vascular endothelium, we generated mice with endothelium-specific deletion of NF2 (NF2 ECKO) by crossing NF2flox/flox mice with tamoxifen-inducible endothelial-specific Cre mice [Cdh5(PAC)-CreERT2]. Endothelium-dependent relaxations to acetylcholine (Ach) were assessed in aortas from NF2 ECKO and wild type (WT) littermates, fed a control and a high fat diet (60 kcal% fat) for 20 weeks. NF2 signalling and endothelial function were also assessed in small visceral fat arteries (VFA) isolated from 18 obese and 18 age-matched healthy subjects undergoing bariatric surgery and cholecystectomy, respectively. Gene in silencing of NF2 by siRNA was performed in VFA from obese patients. Results: In HAECs, PA promoted NF2 activation by decreasing its phosphorylation at Ser518. Akt and MYPT-1 were responsible for NF2 dephosphorylation. In PA-treated HAECs, NF2 was mainly found in the plasma membrane as compared to other cell fractions. Among different membrane proteins implicated in endothelial homeostasis, NF2 binds and activates Caveolin 1 (Cav-1), a pivotal repressor of endothelial NO synthase (eNOS). NF2 knockdown in PA-treated HAECs prevented eNOS–Cav-1 interaction, thus preserving eNOS activity and NO levels. By contrast, HAECs expressing the constitutive active mutant form of NF2 displayed reduced eNOS activity. In aortas from obese mice, we found that NF2-Cav-1 interaction was responsible for impaired eNOS activity and ED. Cav-1 gene silencing in NF2-overexpressing aortas prevented ED, thus confirming the direct involvement of Cav-1 in NF2-induced ED. Interestingly, Ach-dependent vasorelaxation was preserved in obese NF2 ECKO mice as compared to WT littermates. Moreover, NO bioavailability was preserved in aortas from NF2 ECKO mice. In VFA from obese patients, NF2 was upregulated, and its activity negatively correlated with Ach-dependent vasorelaxation. Of note, NF2 gene silencing in VFA from obese patients rescued ED. Conclusions: In human endothelial cells, mice with endothelium-specific deletion of NF2 and VFA from obese patients, we show that NF2 drives ED by repressing Cav-1. Targeting NF2 may prevent ED in obese patients. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Holcim Stiftung